2017
DOI: 10.1161/hypertensionaha.116.07110
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Endothelial Transient Receptor Potential Vanilloid Type 4 Channel and Small-Conductance of Ca 2+ -Activated K + Channels Underpins Impaired Endothelium-Dependent Hyperpolarization in Hypertension

Abstract: V ascular endothelial cells play an important role in the regulation of vascular tone through the release of both vasorelaxing and vasoconstricting factors.1 Apart from the release of vasorelaxant factors such as nitric oxide and prostaglandins, endothelial cells relax the vascular smooth muscle cells through the generation of endothelium-dependent hyperpolarization (EDH). With respect to EDH, there is consensus that the activation of the small-and intermediate-conductance of Ca 2+ -activated K + channels (SK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
59
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 50 publications
(68 reference statements)
11
59
3
Order By: Relevance
“…TRPV4 channels expressed in the vasculature serve as molecular detectors and transducers of arteriole myogenic responses (e.g., mechanical stress; Kim et al, 2015). Numerous studies support an important role for endothelial TRPV4 channel-mediated arteriole dilation (Bagher et al, 2012;Marrelli, O'Neil, Brown, & Bryan Jr, 2007;Seki et al, 2017;Sonkusare et al, 2012;Zhang & Gutterman, 2011;Zhang, Papadopoulos, & Hamel, 2013;Zou, Leung, & Vanhoutte, 2015). However, in some vascular beds, TRPV4 channel activation can evoke constriction (Saifeddine et al, 2015;Soni, Peixoto-Neves, Matthews, & Adebiyi, 2017;Zhang et al, 2018).…”
mentioning
confidence: 99%
“…TRPV4 channels expressed in the vasculature serve as molecular detectors and transducers of arteriole myogenic responses (e.g., mechanical stress; Kim et al, 2015). Numerous studies support an important role for endothelial TRPV4 channel-mediated arteriole dilation (Bagher et al, 2012;Marrelli, O'Neil, Brown, & Bryan Jr, 2007;Seki et al, 2017;Sonkusare et al, 2012;Zhang & Gutterman, 2011;Zhang, Papadopoulos, & Hamel, 2013;Zou, Leung, & Vanhoutte, 2015). However, in some vascular beds, TRPV4 channel activation can evoke constriction (Saifeddine et al, 2015;Soni, Peixoto-Neves, Matthews, & Adebiyi, 2017;Zhang et al, 2018).…”
mentioning
confidence: 99%
“…Rings (1.2 mm) with intact endothelium were placed in 5‐mL organ chambers filled with 36°C Krebs solution that had been aerated with 93% O 2 to 7% CO 2 (pH 7.4). Isometric contractile responses were recorded, as described . The rings were then allocated to 1 of the following treatments: (1) control, (2) indomethacin (10 −5 mol/L), and (3) indomethacin (10 −5 mol/L) and N ω ‐nitro‐ l ‐arginine (L‐NAME; 10 −4 mol/L).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the release of several vasoactive factors, such as nitric oxide (NO) and prostacyclin, vascular endothelial cells regulate arterial tone through the generation of endothelium‐dependent hyperpolarization (EDH) . Although the mechanisms of endothelial dysfunction in hypertension seem to vary, we have demonstrated that the impaired EDH generation accounts for the decreased endothelium‐dependent relaxation of mesenteric arteries of spontaneously hypertensive rats (SHRs), the most commonly used animal model for human essential hypertension . Reduced EDH‐mediated responses have also been reported in the mesenteric arteries of rats with chronic heart failure …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In stroke prone spontaneously hypertensive rats, TRPV4 and SK channel expression in the EC was significantly reduced compared to its normotensive control. 36 However, acetylcholine induced vasodilation was not different. The mechanism for this is still unclear, but it may be due to compensatory ER calcium release in the rats'…”
mentioning
confidence: 91%